2007
DOI: 10.1088/1126-6708/2007/10/108
|View full text |Cite
|
Sign up to set email alerts
|

Near BPS Wilson loop in β-deformed theories

Abstract: We propose a definition of the Wilson loop operator in the N = 1 β-deformed supersymmetric Yang-Mills theory. Although the operator is not BPS, it has a finite expectation value at least up to order (g 2 N) 2 . This does not happen generally for a generic non-BPS Wilson loop whose expectation value is UV divergent. For this reason we call this a near-BPS Wilson loop and conjecture that its exact expectation value is finite. We derive the general form of the boundary condition satisfied by the dual string world… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 41 publications
(82 reference statements)
3
19
0
Order By: Relevance
“…In fact, the real β-deformed theory has been studied extensively (see [18] for a review in the context of AdS/CFT integrability) and, in several cases, has been found to resemble closely, although non-trivially, the results of its undeformed parent theory. For example, the expectation values of particular BPS-like Wilson loops [19] remain undeformed. Moreover, a Lax pair for the real β-deformation was explicitly constructed in [20] by relating the deformed system to the undeformed one, therefore establishing integrability.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the real β-deformed theory has been studied extensively (see [18] for a review in the context of AdS/CFT integrability) and, in several cases, has been found to resemble closely, although non-trivially, the results of its undeformed parent theory. For example, the expectation values of particular BPS-like Wilson loops [19] remain undeformed. Moreover, a Lax pair for the real β-deformation was explicitly constructed in [20] by relating the deformed system to the undeformed one, therefore establishing integrability.…”
Section: Introductionmentioning
confidence: 99%
“…Our choice can be justified from several points of view. It has been found that the 1/4 BPS-like Wilson loop in the β deformed theory in the strong coupling limit has undeformed expectation value [13]. This has also been proved in the case of higher representation Wilson loops in [14].…”
Section: ∆θ Ef F Up To Third-order In the Angle Expansionmentioning
confidence: 69%
“…In this paper we have calculated the cusp anomalous dimension of the Wilson loop in β deformed gauge/gravity duality. An interesting feature of this theory is that several BPS-like quantities, have an undeformed expectation value in the strong coupling limit, for example as [13,14]. This fact enables us to make a conjecture for the from of the cusp anomalous dimensions for every λ.…”
Section: Discussionmentioning
confidence: 99%
“…In this note we will consider gluon and gluino scattering amplitudes and the corresponding light-like Wilson loops in large N β-deformed N = 4 SYM with real β (for a discussion of Wilson loops in the β-deformed theory see [12]). This deformation breaks the N = 4 supersymmetry to N = 1.…”
Section: Introductionmentioning
confidence: 99%